Structural and Chemical Characterization of Cerium Oxide Thin Layers Grown on Silicon Substrate. (2015) - Potin, V.; Lavkova, J.; Bourgeois, S.; Dubau, M.; Matolinova, I.; Matolin, V.
Abstract: In this study, we report transmission electron microscopy and electron energy loss spectroscopy study of cerium oxide thin layers deposited on silicon substrate. Transmission electron microscopy experiments have revealed the flat morphology of the deposited layers. In addition, studies of high resolution images have indicated the presence of mainly ceria crystallized nanoparticles. Energy electron loss spectroscopy measurements were also performed in scanning mode to study the evolution of the cerium valence. In addition to Ce 4+ inside the layer, the presence of amorphous cerium silicate with valence +3 is pointed out at the vicinity of the substrate.